A king's ransom / 2. - Watson, Jude (39 clues. Cahills vs. Vespers, 2011)
Thirteen-year-old Dan Cahill and his older sister Amy race against time to find an ancient map that has not been seen for half a century and use it to redeem their family members who have been kidnapped by a sinister organization called the Vespers.